Norwegian det-constructions and their translation correspondences in English and German acontrastive corpus based study of dummy subjects - Chocholoušová, Bohumila (2007)
The aim of this thesis is to introduce a multiple parallel corpus project set up by the University of Oslo. The main research areas behind this project concern contrastive language typology of individual syntactic, lexical and textual devices employed in information processing on the sentence level, as well as discourse structuring on the text level. The languages in focus are Norwegian, English, and German. In a case study of dummy subjects, I will attempt to illustrate that individual construction types often reveal interesting similarities, as well as differences, between the investigated languages. The syntactic patterns under study are often interrelated and the analysis of sentence form in the light of contrastive data often requires a holistic approach treating the level of syntax, lexis and discourse semantics as joint premises. In the article below, I will briefly explore such syntactic patterns as presentatives, clefts, impersonal passives, specifying constructions, extraposi.